Smart Phone/Device Application to Improve Delivery of Enteral Nutrition in Adult Patients Admitted to the Medical Intensive Care Unit. (January 2019) - Mahmood, Sultan; Hoffman, Leah; Ali, Ijlal Akbar; Zhao, Yan D; Chen, Allshine; Allen, Karen
Background: Resident physicians are frequently uncomfortable ordering enteral nutrition (EN) and are unaware of the variety of formulas and supplements available for different disease processes. Many depend on a clinical dietician to assist with recommending EN formulas and patient energy requirements that may not be readily available on patient admission. This creates a barrier to early initiation of EN and non-compliance with Society of Critical Care Medicine and American Society of Parenteral and Enteral Nutrition clinical guidelines. Objective: Internal medicine resident physicians were provided an iPod with a smart phone/device application (EN application) to assist them in choosing EN formulas for patients during their intensive care unit (ICU) rotation. The primary outcome was improved initiation of EN within 24 hours of admission. Secondary outcomes included the following: time to initiate EN, goal calories reached, infections rates, length of stay, mortality, and concordance with clinical guidelines. Design: The study is a quasi-experimental design to improve delivery of EN at an academic medical center in the medical ICU. Data were collected from a retrospective chart review to evaluate the impact of an EN application to assist resident physicians when ordering EN. Results: Use of the EN application reduced the percent of patients with delayed initiation of EN from 61.2% prior to 37.5% ( P  < .01). The mean time to initiate EN also improved 44.5 vs 31.9 hours ( P  < .01). Patients were also more likely to achieve their daily caloric goal ( P  < .01). Conclusion: The use of an EN application to assist internal medicine residents when ordering EN reduced delays in initiation of EN and improved overall delivery of EN to medical ICU patients.